Analisis Pengaruh Diameter Lilitan dan Variasi Jumlah Lilitan Terhadap Efisiensi Generator Sinkron Magnet Permanen 24 Slot 16 Pole - Putra, Reza Junius; Gusnita, Novi (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
The need for electrical energy is a basic need that cannot be eliminated in the daily lives. With the increase in population, the need for electrical energy increases every year. Non-renewable energy has many examples, such as coal, oil, gas and so on. Wind energy is an alternative energy whose availability in nature. To convert wind energy into electrical energy, a Wind Power Plant is needed. In the conversion process using a generator. A generator that can be used is the Permanent Magnet Synchronous Generator 24 Slot 16 Pole (PMSG) which can produce magnetic flux and is suitable for use because with low rotation it can produce good efficiency to overcome areas with low wind speeds in Indonesia. To design and test through simulation with infolytica Magnet software based on the Finite Element Method. To increase efficiency in PMSG, this research analyze the effect of coil wire and the number of coils with coil wire diameters of 4 mm2, 6 mm2 and 8 mm2. For the number of coils starting from 25, 30 and 35 coils using a speed of 500 rpm and a load of 10 Ohms equalize all variations. Where the highest efficiency is 88.2%, the output power is 1609.4 Watt, the input power is 1842.0 Watts, the current is 12.49 Amperes and the voltage is 124.9 Volts, obtained on a wire area of 8 mm2 and a number 35 turns with an efficiency of 87.1%.Keywords - PLTB, Lilitan, Generator, Efficiency, Energy